2012
DOI: 10.5607/en.2012.21.2.68
|View full text |Cite
|
Sign up to set email alerts
|

Neurochemical Properties of Dental Primary Afferent Neurons

Abstract: The long belief that dental primary afferent (DPA) neurons are entirely composed of nociceptive neurons has been challenged by several anatomical and functional investigations. In order to characterize non-nociceptivepopulation among DPA neurons, retrograde transport fluorescent dye was placed in upper molars of rats and immunohistochemical detection of peripherin and neurofilament 200 in the labeled trigeminal ganglia was performed. As the results, majority ofDPA neurons were peripherin-expressing small-sized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 29 publications
4
9
0
Order By: Relevance
“…The optimal goal of regenerative endodontics is to regenerate the pulp tissue. The present study showed no pulp regeneration as revealed by absence of immuno-reactivity to nestin, which detects the neuronal derivatives of the neural crest that comprises the dental pulp [ 19 , 20 ]. Treatment modalities will change in teeth with regenerated roots and regenerated pulps as compared to teeth with regenerated roots and no regenerated pulps.…”
Section: Discussionmentioning
confidence: 90%
“…The optimal goal of regenerative endodontics is to regenerate the pulp tissue. The present study showed no pulp regeneration as revealed by absence of immuno-reactivity to nestin, which detects the neuronal derivatives of the neural crest that comprises the dental pulp [ 19 , 20 ]. Treatment modalities will change in teeth with regenerated roots and regenerated pulps as compared to teeth with regenerated roots and no regenerated pulps.…”
Section: Discussionmentioning
confidence: 90%
“…In this study, peripherin immunoreactivity was identified in the soft connective tissue within the pulp chamber and canals. Peripherin is highly enriched in neuronal derivatives of the neural crest, the embryological tissue from which the dental ectomesenchyme derives (65), and plays a role in neurite elongation during development and axonal regeneration cells (66). Lastly, we showed Wnt1a immunoreactivity is present throughout the restored soft connective tissue found within the pulp chambers, suggesting that Wnt activation is locally available and thus may exercise a role in promoting regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Some 5-HT3-receptor-positive fibers contained neurofilaments (Fig. 6F), a neurochemical marker of myelinated A-fibers (Bae et al, 2015;Vang et al, 2012), whereas others did not (not shown). Taken together, these results suggested a major role of 5-HT3 receptors in activation of the trigeminal nerve terminals by 5-HT.…”
Section: Receptor Mediating the Peripheral 5-ht Effectmentioning
confidence: 94%